Achieving Sustainable Development Goals in Conditions of Rational Expectations by Achieving a Balance of Interests of Education and Production in the Field of Light Industry During Troubled Times of Pandemic and War - Ripka, Galyna; Bielousov, Yaroslav; Maznev, Ievgen (Problemy Ekorozwoju, 2024)
The article presents a comprehensive analysis of the global consequences caused by the development of light industry for achieving the Sustainable Development Goals. The ecological context allows us to focus on how light industry affects climate change, resource depletion, waste generation and water pollution. It is emphasized that the impact of light industry can create significant challenges for sustainable development related to SDG 13 (Climate action), SDG 6 (Clean water and sanitation), SDG 12 (Responsible consumption and production), SDG 14 (Life below water) and SDG 15 (Life on land). The article also examines the socio-economic context, discusses how light industry leads to persistent inequality, loss of traditional skills and cultural heritage, as well as trade imbalance. In terms of social responsibility, light industries have a history of violations of working conditions and labour rights. The socio-economic impacts considered may hinder the achievement of SDGs such as SDG 5 (Gender equality), SDG 8 (Decent work and economic growth), SDG 9 (Industry, innovation and infrastructure), SDG 10 (Reduced inequalities), SDG 11 (Sustainable cities and communities) and SDG 12 (Responsible consumption and production), SDG 17 (Partnerships for the goals). The theory of rational expectations is used to predict the development of light industry and its subsequent impact on sustainable development in the post-pandemic period. The prospects of applying the theory in the training of specialists for light industry are substantiated. The impact of the consequences of the pandemic and the war in Ukraine on the decision-making processes in light industry and their alignment with the sustainable development goals, taking into account civilizational challenges, is considered. In the process of research, an econometric model has been developed to determine the desired balance of interests between education and production based on rational expectations in a sustainable development environment. It advocates harmony between these two aspects, based on rational expectations, to promote sustainable development. This balance is crucial for achieving SDG 4 (Quality Education), SDG 9 (Industry, Innovation and Infrastructure) and SDG 17 (Partnerships for the goals). The properties of the model provide a wide range of applications, allowing to estimate the impact of a variety of factors on sustainable development in light industry. The developed model can be applied to estimate the values of the dependent variable for individual countries or regions, as well as to analyse the influence of independent and control variables on changes in its value. As a planning tool, the model can be adapted to develop context-sensitive sustainability strategies in light industries. The article offers ideas and practical solutions for using the potential of light industry in the pursuit of sustainable development in conditions of rational expectations.